Impact of medication use on olfactory performance in older adults - Izco-Cubero, Maite; Zambom-Ferraresi, Fabiola; Zambom-Ferraresi, Fabricio; de la Riva, María Luisa Fernández González; Santamaría, Enrique; Fernandez-Irigoyen, Joaquín; Lachén-Montes, Mercedes; Lasarte, Juan Jose; Uzcanga-Lacabe, Maria; Fernandez, Secundino; Martin, Gloria Sanjurjo San; Maraví-Aznar, Enrique; et al. (Frontiers in Public Health, 2025)
IntroductionOlfactory dysfunction impacts quality of life, safety, and nutrition. Despite its relevance among older adults, the role of medications in influencing olfactory performance remains understudied. This research investigates whether olfactory alterations in older adults are associated with the type or number of medications prescribed.MethodsAn observational cross-sectional study was conducted with 107 participants (mean age of 86.1 ± 5.1 years). Olfactory performance was evaluated using the Sniffin’ Sticks Test (SST). Functional capacity, cognitive function and the number and type of medications were also assessed.ResultsThe analysis demonstrated a correlation between better olfactory performance and higher cognitive function. An inverse correlation was found between the age of participants and olfactory identification. While polypharmacy (intake of five or more medications) did not show a significant association with olfactory dysfunction, the intake of laxatives was associated with poorer olfactory threshold performance (−1.21, 95% CI −2.07 to −0.34; p = 0.008). In contrast, proton pump inhibitors (PPIs) (1.14, 95% CI 0.07 to 2.21; p = 0.04) and vitamin D (1.09, 95% CI 0.03 to 2.15; p = 0.04) intake were linked to improved olfactory identification.DiscussionThese findings suggest that certainmedications influence olfactory performance; however, further research is needed to clarify the effects of different drug classes on olfaction.